Faktor Determinan Kesiapsiagaan Perawat Terhadap Bencana Gunung Meletus (Gamalama) di Puskesmas Wilayah Kerja Dinas Kesehatan Kota Ternate - Hakim Husen, Abd; Kaelan, Cahyono; Nurdin, Armyn; J. Hadi, Anto (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Puskesmas is part of the government and is obliged to perform its functions in disaster preparedness. This study aimed to determine the description and the relationship of determinant factors of nurse preparedness to the eruption of Mountain Gamalama at the working area of the Health Center in ​​Ternate City Health Office. The research used the combined research method (Mixed Method), which was the combination between the quantitative method and the qualitative method. The research samples included all the nurses in the Health Center of the working area of the Health office of Ternate City comprising 41 people. The data analysis was conducted using the Chi-square test for quantitative research. The Knowledge variable was p=0,05, and the skill variable was p= 0,171. The related to the preparedness. Meanwhile, the qualitative research was in the form narration of the interviews with the respondents who had low skills because of the little training and stimulation about the calamity.